The Influence of Hen Age on Hatching Egg Quality and Embryonic Development of Sentul Chickens - Azizah, Dinda; Ulfah, Maria; Fahrudin, Mokh (Bogor Agricultural University, Indonesia, 2025)
Sentul chicken is a local Indonesian chicken primarily raised for meat production. One crucial factor affecting egg quality and embryo development is hen age. This study aims to examine the influence of hen age on the external and internal quality of Sentul chicken hatching eggs, as well as the early development of the embryo. Eggs from 41-week-old and 78-week-old hens were compared across exterior and interior quality, nutrient composition, and embryonic development. Data analysis was performed using a descriptive method for hatching egg quality and a t-test for embryonic development. Results revealed that eggs from older hens (78 weeks) were significantly (P<0.05) heavier, had a higher egg shape index, and exhibited higher albumen and yolk indices, as well as a higher Haugh unit (HU). Nutrient analysis showed an increase in protein and fat content in older hens’ eggs, alongside a reduction in water content. However, embryonic development assessed by primitive streak and somite formation showed no significant differences (P>0.05) between the age groups. These findings highlight the positive influence of hen age on egg quality and embryonic development, potentially enhancing hatchability and chick development. Further research is, however, needed to observe long-term effects of hen age on embryo development and post-hatch performance.